1980
DOI: 10.1128/iai.28.3.649-653.1980
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated neutralization of virus is abrogated by mycoplasma

Abstract: The ability of a mouse mammary tumor cell line to abrogate antibody neutralization of vesicular stomatitis virus was shown to be due to the presence of mycoplasma. The mycoplasma was isolated from the cell line and typed as Mycoplasma orale. Colonies of this mycoplasma were used to deliberately infect cell cultures which then gained the capacity to reactivate antibody-neutralized virus. The extent of the reactivation depended on the source of neutralizing antiserum. Other species of mycoplasma were tested and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Interestingly, two studies serendipitously evidenced the generalized degradation of immunoglobulins by mycoplasmas in contaminated cell cultures. In 1980, Dickson et al reported that Mycoplasma orale , Mycoplasma arginini , and Mycoplasma hyorhinis were able to abrogate the neutralization of vesicular stomatitis virus particles by sheep antiserum ( 100 ). The origin of this activity was not identified at the time, but the authors proposed that “the mycoplasma could excrete or have on its surface proteases […] which are capable of destroying the antigen-antibody complexes.” In 2016, Hirayasu et al reported that M. hyorhinis was able to cleave off the V H domain of nonspecific IgM, IgA, and IgG, probably through MIB-MIP, with up to 50% of the antibodies present in the culture media being degraded ( 82 ).…”
Section: Putative Functions Of Mycoplasma Immunoglobulin-blocking Proteinsmentioning
confidence: 99%
“…Interestingly, two studies serendipitously evidenced the generalized degradation of immunoglobulins by mycoplasmas in contaminated cell cultures. In 1980, Dickson et al reported that Mycoplasma orale , Mycoplasma arginini , and Mycoplasma hyorhinis were able to abrogate the neutralization of vesicular stomatitis virus particles by sheep antiserum ( 100 ). The origin of this activity was not identified at the time, but the authors proposed that “the mycoplasma could excrete or have on its surface proteases […] which are capable of destroying the antigen-antibody complexes.” In 2016, Hirayasu et al reported that M. hyorhinis was able to cleave off the V H domain of nonspecific IgM, IgA, and IgG, probably through MIB-MIP, with up to 50% of the antibodies present in the culture media being degraded ( 82 ).…”
Section: Putative Functions Of Mycoplasma Immunoglobulin-blocking Proteinsmentioning
confidence: 99%